Pengaruh Dana Zakat Produktif Dan Pemberdayaan Mustahiq Terhadap Laba Usaha Mustahiq Di Kabupaten Aceh Utara (Studi Kasus Baitul Mal Kabupaten Aceh Utara) - Soraya, Nada; Mukhlis; Abdul Halim; Rusydi; Muhammad Suip (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2023)
This study aims to determine productive zakat funds and mustahiq empowerment on mustahiq operating profits. By using secondary data and primary data. The method used is quantitative research using a field survey research design. The results showed that the distribution under study was group criteria with each sub-district having one group, based on the results, with the addition of modah from the Baitul Mal of North Aceh Regency it was able to increase mustahiq's operating profit and mustahiq's welfare. Empowerment (guidance, training and coaching) is being carried out to increase the mustahiq's operating profit and maintain the mustahiq's business with the aim that the mustahiq is able to be independent and not fall again